Research is still limited on nutrition and quality of life among older adults - Arensberg, Mary Beth; Gahche, Jaime; Clapes, Raquel; Kerr, Kirk W.; Merkel, Joyce; Dwyer, Johanna T. (Frontiers in Medicine, 2023)
Globally, the number of older adults is growing exponentially. Yet, while living longer, people are not necessarily healthier. Nutrition can positively impact healthy aging and quality of life (QoL). Two decades ago, nutrition and diet were rarely viewed as key QoL domains, were not part of QoL screening, and QoL studies frequently used unvalidated tools. It is unclear how the nutrition and QoL research area may have since evolved.Methods: A scoping review was conducted in Pubmed of research with community-living older adults (aged >65) from developed economies that included 1 of 29 common, valid QoL instruments, nutrition indices, and was published between 1/2000-12/2022. The review followed published methodology guidance and used the Preferred Reporting Items for Systematic Reviews and Metaanalyses (PRISMA) flow diagram to document identified studies and record number of included/excluded studies (based on scoping review's pre-specified criteria).Results: Of 258 studies identified initially, 37 fully met scoping review inclusion criteria; only 2 were QoL studies, 30 focused on nutrition, 3 on measurement tool validation/testing, and 2 were other study types. Most studies (n=32) were among populations outside of North America; majority were conducted in Europe (n=22) where the EuroQol 5 Dimension (Eq5D) was used in >1/2 the studies. Of 5 North American studies, the 36-Item Short Form Survey (SF-36) was most frequently used (n=4). Myriad nutrition indices described various aspects of eating, dietary intake, and nutrition status, making comparability between studies difficult. Studies included several different nutrition questionnaires; Mini Nutritional Assessment (MNA) (n=8) or Mini Nutritional Assessment Short Form (MNA-SF) (n=5) were used most frequently. The most frequent anthropometric measure reported was Body Mass Index (BMI) (n=28). Nutrition-related biochemical indices were reported infrequently (n=8).The paucity of studies over the last two decades suggests research on nutrition and QoL among community-living older adults remains underdeveloped. Valid QoL instruments and nutrition indices are now available. To ensure greater comparability among studies it is important to develop consensus on core indices of QoL and particularly nutrition. Greater agreement on these indices will advance further research to support healthy aging and improve QoL for communitydwelling older adults.